Hi-Viz Florescent SOTRA - Noralisa, Ismail; Norazlina, Rahmat; Norzaidah, Ngali; Norazidah, Shamsudin (Faculty of Information Management, UiTM Puncak Perdana, 2015)
Missing important documents while travelling might create disastrous problems as it can affect traveling enjoyment. When travel, people will carry several items such as identification card, passport, flight ticket, boarding pass, credit card, cash, ATM cards and mobile phone. This can create a possibility of misplace or worse, missing things especially for disorganized people. Therefore, a proper new travel organizer can help travelers to place all their belongings for easy retrieval. The main product feature is a multi-size compartment to store different things while traveling. Another important element is it’s made from a combination of traditional Malay songket and glow in the dark fabric as a covering theme. The decision to choose songket as a theme is due to the current usage of this fabric. Nowadays, the use of songket is limited to special occasions only such as wedding, cultural performance and festive season like Aidilfitri celebration. Meanwhile, glow in the dark fabric used to ease the process of searching for travel organizer in traveler’s bag or luggage. Travel organizer been chosen as an instrument for promoting songket because it been widely used by travellers who travel locally and internationally. This could be further realized through collaboration with local airlines such as Malaysia Airlines. As a conclusion, SOTRA could be a solution for proper storage of travel items and help to promote and ensure the sustainability of songket.